Epistemological Beliefs, Digital Literacy, and Cultural Attitudes in Shaping Students Entrepreneurial Knowledge - Marleni; Disman; Harri Mulyadi; Neiny Ratmaningsih; Cicilia Melinda; Suehartono Syam; Siti Fathimah; Siti Kulsum (Ital Publication, 2026)
The development of higher education in the digital era presents new challenges for students, particularly in developing entrepreneurial competencies that are relevant to global needs while also rooted in local cultural values. The integration of cognitive aspects, digital skills, and cultural attitudes is becoming increasingly important in producing a young generation capable of innovating and competing in the face of globalization. Although various previous studies have highlighted the role of epistemological beliefs, digital literacy, and cultural attitudes separately, studies that integrate all three within the framework of strengthening entrepreneurial knowledge are still limited, especially in Indonesia. This study investigates the impact of epistemological beliefs and digital literacy on shaping students' cultural attitudes and entrepreneurial knowledge within the context of higher education in Indonesia. Using a quantitative approach and an explanatory survey method, data were collected from 398 students and analyzed using Structural Equation Modelling with Partial Least Squares (SEM-PLS). The results indicate that epistemological beliefs have a significant and positive impact on digital literacy, cultural attitudes, and entrepreneurial knowledge, thereby confirming their pivotal role in the development of entrepreneurial competencies. Digital literacy also has a significant, albeit relatively weaker, influence on cultural attitudes and entrepreneurial knowledge. Furthermore, cultural attitudes proved to be a significant mediator, strengthening the relationship between cognitive and digital factors and entrepreneurial achievement. This research model demonstrated high predictive power, accounting for 69.0% of the variance in entrepreneurial knowledge. These findings enrich the literature by integrating cognitive, technological, and cultural dimensions into a comprehensive framework for entrepreneurship education.